2015
DOI: 10.1136/jech-2015-205954
|View full text |Cite
|
Sign up to set email alerts
|

The association between green space and depressive symptoms in pregnant women: moderating roles of socioeconomic status and physical activity

Abstract: BackgroundThe current study explored the association between green space and depression in a deprived, multiethnic sample of pregnant women, and examined moderating and mediating variables.Method7547 women recruited to the ‘Born in Bradford’ cohort completed a questionnaire during pregnancy. A binary measure of depressive symptoms was calculated using a validated survey. Two green space measures were used: quintiles of residential greenness calculated using the normalised difference vegetation index for three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
191
5
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 254 publications
(222 citation statements)
references
References 34 publications
22
191
5
4
Order By: Relevance
“…For example, McEachan et al tested whether the relationship between NDVI and peripartum depression differed by physical activity level, and found that the beneficial effect of greenness was stronger in those who were physically active, only in the 300 m buffer 9. There was no evidence of effect modification by physical activity in their analysis concerning proximity to a major green space.…”
Section: Resultsmentioning
confidence: 99%
“…For example, McEachan et al tested whether the relationship between NDVI and peripartum depression differed by physical activity level, and found that the beneficial effect of greenness was stronger in those who were physically active, only in the 300 m buffer 9. There was no evidence of effect modification by physical activity in their analysis concerning proximity to a major green space.…”
Section: Resultsmentioning
confidence: 99%
“…For example, in a prospective study of individuals with diabetes, NDVI was associated with a lower risk of depression, however, density of parks/recreational space did not influence depression [39]. In another study of pregnant women in Bradford, United Kingdom, those who resided in the 3 rd or higher quintiles of greenness were 18–23% less likely to report depressive symptoms [27]. Moreover, stronger effect for greenness were estimated among those who were disadvantaged and physically inactive.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, designers and planners should work with GI researchers to find the optimal types and sizes of GI to implement for both ecological and human health purposes. Finally, because GI benefits several population types, designers should infuse urban areas with trees, green spaces, and other forms of GI so that workers [19], students [13], mothers [90], and people who have mental issues [32] have easy access to GI.…”
Section: Discussionmentioning
confidence: 99%